Analisis Keamanan Sistem Informasi Pada Perusahaan E-Commerce Di Indonesia - Tise Warniwati Zebua; Joni April Zebua (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
E-commerce is a trading activity carried out online by utilizing the internet in its business. This research aims to analyze information system security in e-commerce companies in Indonesia. With the rapid growth of the e-commerce industry, data and information security has become a crucial issue that needs to be addressed by business people. The research methods used include qualitative analysis and surveys of several leading e-commerce companies. The research results show that many companies still face challenges in protecting customer data, managing the risk of cyber attacks, and complying with data security regulations. Apart from that, awareness of the importance of information security also needs to be increased among employees. This research is expected to provide practical recommendations for improving information system security in e-commerce companies in Indonesia.